2006
DOI: 10.1152/ajpregu.00729.2005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sex on perception of rectosigmoid stimuli in irritable bowel syndrome

Abstract: In irritable bowel syndrome (IBS) patients, the relationship between sex and sensitivity to visceral stimuli is incompletely understood. Our aim was to evaluate the effect of sex on perceptual responses to visceral stimulation in IBS. Fifty-eight IBS patients (mean age 42+/-1 yr; 34 men, 24 women) and 26 healthy controls (mean age 38+/-3 yr; 9 men, 17 women) underwent barostat-assisted distensions of the rectum and sigmoid colon. Rectal discomfort thresholds were measured using a randomized, phasic distension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
79
3
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 55 publications
(88 reference statements)
10
79
3
1
Order By: Relevance
“…Using validated psychophysiological techniques, we have previously reported that women with IBS show greater subjective emotional and perceptual responses to colorectal distension than male patients or healthy men or women (Chang et al, 2006a). One may speculate that the sex-related differences in the connectivity of the "emotional-arousal" network seen in the current study may be related to these greater emotional and perceptual responses previously reported.…”
Section: Possible Correlation Of Findings With Sex Differences In Behsupporting
confidence: 60%
“…Using validated psychophysiological techniques, we have previously reported that women with IBS show greater subjective emotional and perceptual responses to colorectal distension than male patients or healthy men or women (Chang et al, 2006a). One may speculate that the sex-related differences in the connectivity of the "emotional-arousal" network seen in the current study may be related to these greater emotional and perceptual responses previously reported.…”
Section: Possible Correlation Of Findings With Sex Differences In Behsupporting
confidence: 60%
“…With respect to visceral pain, a lower pain threshold to esophageal distension was demonstrated in females [149], whereas rectal stimulation studies showed no gender differences in mechanical thresholds [11,186], or higher thresholds in healthy women [34]. Additionally, women have shown larger referred pain areas to the mechanical and thermal stimulation of the esophagus [161].…”
Section: What Types Of Pain Tests Are Appropriate? Human Studiesmentioning
confidence: 99%
“…For instance, evaluation of pain sensitivity at asymptomatic body sites can reveal information about general pain-processing alterations, as has been shown for fibromyalgia [118,189], various types of headaches [182], and temporomandibular disorders (TMD) [175]. Additionally, experimental provocation of a patient's clinical pain allows separate assessment of that pathological condition, for instance evaluating pressure pain sensitivity of symptomatic muscles of fibromyalgia patients [188], or rectosigmoid distension of irritable bowel syndrome patients [34].…”
Section: What Types Of Pain Tests Are Appropriate? Human Studiesmentioning
confidence: 99%
See 2 more Smart Citations